2020
DOI: 10.1080/01635581.2020.1770812
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Nutrition Formulas for Patients Undergoing Surgery for Colorectal Cancer: A Bayesian Network Analysis

Abstract: Optimal nutrition formulas for colorectal cancer patients underwent surgery remains uncertainty. We constructed an indirect comparison study to assess comparative efficacy of different immunonutrition formulas and standard nutrition in colorectal cancer patients underwent surgery. PubMed, the Cochrane Library, EMBASE, ClinicalTrials.gov and Web of Science databases were searched to identify RCTs that compared immunonutrition with standard nutrition or different immunonutrition formulas. Data on length of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A study of 205,840 oncologic operations by McKenna et al [10] reported that the optimal definition of malnutrition varied by cancer type and that there was not a one-size-fits-all approach. A recent indirect comparison study of different immunonutrition formulas in patients undergoing surgery for colorectal cancer con- cluded that glutamine had some superiority for reducing complications and hospital stays, but ultimately determined that the results were close enough that large scale randomized controlled trials would be required [2]. Some institutions have even adopted "surgical wellness" programs to optimize medical conditions, which included providing immune-nutrition supplements and were found to reduce length of stay following pancreatectomy [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 205,840 oncologic operations by McKenna et al [10] reported that the optimal definition of malnutrition varied by cancer type and that there was not a one-size-fits-all approach. A recent indirect comparison study of different immunonutrition formulas in patients undergoing surgery for colorectal cancer con- cluded that glutamine had some superiority for reducing complications and hospital stays, but ultimately determined that the results were close enough that large scale randomized controlled trials would be required [2]. Some institutions have even adopted "surgical wellness" programs to optimize medical conditions, which included providing immune-nutrition supplements and were found to reduce length of stay following pancreatectomy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate preoperative nutritional status has been found to be an important factor in reducing surgical complication, morbidity, and mortality [1][2][3][4][5][6][7][8][9][10]. Thus, preoperative nutritional screening and subsequent optimization may be useful for many groups of patients, especially those undergoing surgery in the setting of cancer or comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian networks (BNs) [188] are a long-standing form of statistical network modeling used to reverse-engineer probabilistic causality among variables; with the development of highthroughput sequencing technology, BNs have been widely used to infer causal gene regulatory networks in different diseases [189][190][191][192][193][194]. Recent studies have applied BNs to infer molecular mechanisms and key drivers in Alzheimer's disease [22,128].…”
Section: 7) Bayesian Network Predictive Network and Network Validationmentioning
confidence: 99%
“…After deconvolution, we applied a cutting-edge systems biology approach 23,59,60 to build causal network models of the neuronal component of AD by integrating the deconvoluted neuronspecific RNAseq data with the whole-genome genotype data from the MAYO and ROSMAP datasets. Bayesian networks 61 are a long-standing form of statistical network modeling used to reverse-engineer probabilistic causality among variables; with the development of high-throughput sequencing technology, Bayesian networks have been widely used to infer causal gene regulatory networks in different diseases [62][63][64][65][66][67] . Recent studies have applied Bayesian networks to infer molecular mechanisms and key drivers in Alzheimer's disease 24,68 .…”
mentioning
confidence: 99%